Dwindling status of Epimedium elatum (Morren & Decne) and its geographical distribution in Kashmir Himalaya, India - Mushtaq, Qazi P. Hassan, Sajad A. Lone, Saleem; Gupta, Suphla (Current Botany, 2018)
Epimedium elatum (Morren & Decne) of family Berberidaceace is a rare perennial medicinal plant, endemic to high altitude forests of Northwestern Himalayas in India. Ethnobotanically, it has been used as an ingredient for treatment of bone-joint disorders, impotence and kidney disorders in Kashmir Himalayas. Phytochemically, it is rich in Epimedin ABC and Icariin; all of these have been demonstrated to possess remarkable biological activities like PDE-5 inhibition (treatment of erectile dysfunction), anticancer, antiosteoporosis antioxidant and antiviral properties. The present investigation reports its traditional usage, comprehensive distribution and conservation status from twenty ecogeographical regions in Kashmir Himalayas, India. The species was reported from Gurez valley for the first time. Numerous threats like excessive grazing, deforestration, habitat fragmentation, tourism encroachment, landslides and excessive exploitation have decreased its natural populations in most of the surveyed habitats. Consequently, its existence may become threatened in near future if timely conservation steps are not taken immediately by concerned stakeholders involved in medicinal plant research. Moreover, use of plant tissue culture techniques is recommended for development of its in vitro propagation protocols. Therefore, introduction of this medicinal plant in botanical gardens, protected sites and development of monitoring programmes are needed for its immediate conservation in Northwestern Himalayas, India.